PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI KELURAHAN SINGKIL DUA KECAMATAN SINGKIL KOTA MANADO (Community Participation in Household Waste Management in Singkil Two Village Singkil District, Manado City) - Findy Elisa Sompie; Benu Lisye Suzana Olfie; Jean Fanny Junita Timban (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research was to determine how community participation through the principles of household waste management in Singkil Dua village, Singkil Subdistrict, Manado City, which consists of: waste embodiment patterns, waste collection/transportation, reduction of waste generation, reuse of materials / materials so as not become trash and recycle trash. This research was conducted for three months, starting from SeptemberNovember 2020. the study is carried out in October to December 2021, with data used in primary adn secondary data then descriptive analysisResearch result showed that the equality of people in the management of household garbage in Singkil Dua Citizen participation in the management of the garbage is high enough because of a garbage bank program managed to benefit the public, Judging from the down of three months of garbage is at a total 63 score with a 70% interpretation and is categorized as good. Citizen participation in household waste management in a short kelkil region is seen from the reuse of materials at a total score 47 with an interpretation of 52.2% and is categorized quite well. The participation of society in the management of household garbage in a zero-sum economy is seen from recycling recycling at a total of 45 with an interpretation of 50%, and is categorized quite well. Thus, based on the recapitulation of individual sub-variables of community participation in the management of household garbage in the kelkil singkil sub-district lies ata total score of 312 with a 69.3% interpretation, and is categorized both.